2020
DOI: 10.1101/2020.05.07.081752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial evolution in high osmolarity environments

Abstract: 20 21 52 cell imaging demonstrated that enhanced fitness was coupled to faster growth, and 53 metagenomic sequencing revealed mutations that reflect growth tradeoffs across 54 osmolarities. Our study demonstrates the utility of long-term evolution experiments for 55 probing adaptation during environmental stress.56

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It has been shown earlier that under non-stress conditions, bacteria favor phytohormone synthesis rather than osmolyte accumulation, whereas the opposite occurs under stress conditions. Such a shift in metabolic activity is common in bacterial cells, allowing them to maintain homeostasis when there is an increase in osmotic pressure in the extracellular medium (Varela et al, 2004;Lahtvee et al, 2014;Cesar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown earlier that under non-stress conditions, bacteria favor phytohormone synthesis rather than osmolyte accumulation, whereas the opposite occurs under stress conditions. Such a shift in metabolic activity is common in bacterial cells, allowing them to maintain homeostasis when there is an increase in osmotic pressure in the extracellular medium (Varela et al, 2004;Lahtvee et al, 2014;Cesar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 14, 2021. ; https://doi.org/10.1101/2021.05.13.444061 doi: bioRxiv preprint In general, our work demonstrates that it is feasible to reproduce time series statistics using consumer-resource models of microbiota dynamics, thereby generating mechanistic hypotheses for further investigation. In future work, more detailed hypotheses can be generated by investigating how time series statistics are affected by modifications to baseline CR dynamics, such as the incorporation of metabolic crossfeeding 6,31 , functional differentiation from genomic analysis [32][33][34] , and physical variables such as pH 35,36 , temperature 37 , and osmolality 38 . In addition, recent studies have shown that evolution can substantially affect the dynamics of human gut microbiotas [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…A final consideration is the role of osmotic pressure in altering the efficiency of eDNA uptake. Populations adapting to high osmolarity environments generally have a large fraction of mutations in genes associated with cell wall synthesis (Cesar et al 2020). Therefore, it could be that changes in the cell wall altered the pilus structure which captures eDNA from the environment (Graupner et al 2000).…”
Section: Discussionmentioning
confidence: 99%